Sejarah dan asal-usul bahasa Arab: satu kajian linguistik sejarawi - Hassan Azhari, Abd Rauf (Universiti Putra Malaysia Press, 2004)
This study focuses on the linguistic history of the origin of the Arabic language. This is because until today, the origin of Arabic is still being discussed and studied by the Eastern and Western intellects. This paper will also be discussing the Arabic language that originated from the Semitic language. In this study, the author needs to discuss opinions from Arabic linguistic experts and Western intellects regarding the location and language used by the Samiyyah people. In addition, this paper will also prove that the early location of the Samiyyah people is in the Arab peninsular and the earliest language used was also Arabic language.